Methodological Support for The Development of Primary School Students' Creative Activities (Texas Journal of Multidisciplinary Studies, 2021)
This article has created an article on priority areas of development of the creative activity of primary school students. It also provides complete information about the shortcomings of primary education and the problems that arise there.